Development of textbooks to support merdeka curriculum learning on nanotechnology material for Phase E - Ildyra Fazira; Mawardi Mawardi (Jurnal Pijar Mipa, 2023)
The development of a textbook to support Merdeka curriculum learning on nanotechnology material for phase E high school students is equipped with more detailed material content, multi representations that are easy to understand, and a more attractive book display. It is hoped that it can increase students' learning motivation and abilities due to learning loss due to COVID-19 and support the learning process and education in the era of the industrial revolution 4.0. Ministerial Decree of The Minister of Education and Culture of The Republic of Indonesia No.008/H/KR/2022 concerning chemistry learning outcomes in phase E high school students there is nanotechnology material. This study aimed to develop a valid and practical textbook to support learning for the Merdeka curriculum on phase E nanotechnology material. Research in modern chemistry continues to grow, evidenced by the discovery of nanotechnology, which involves measuring and manipulating matter at the atomic, molecular, and supramolecular levels measured on a scale of 1-100 nm. The research conducted is categorized as an educational design study using the Plomp development model and includes three phases: preliminary research, development or prototyping, and evaluation. Validation analysis resulted in a content effectiveness test score 0.91 for one valid category. At the same time, teacher and student practice tests scored 92% and 92%, respectively, in the highly practical practicality category. In summary, it is effective and practical to develop a textbook for Phase E high school students to support learning the Merdeka curriculum on nanotechnology material.